(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The technology involving the fabrication and pre-assembly of constructional elements and components before they are installed into their final location. The precedent of prefab industry is the significant for the development of new technology in construction business of any nation. The present age demands a great need for affordable and fast housing facilities so the projects need to be completed at competitive fast rates. Conventional construction methods fail to deliver the desired speed of construction. So we opt for some other methods of construction. Total time of construction can be lowered through application of be precast construction. Despite of the advantageous features of fast and speedy erection, low cost precast construction. It is found in the literature review that majority of the research work limited to the static cost analysis and subsequent cost control However, considering that the cost of prefabricated building differs from that of traditional manufacturing industry and construction industry. I can also be seen that the cost influence factors are not only diverse in nature but and the cost relationship is more complex. It can also be seen that cost increase may be as a result of different reasons, or in some cases a single reason may induce several cost increases. In short, the cost rise is a function of the dynamic relation between the diverse cost drivers, and it is necessary to study the effect of a factor on the whole from a scientific perspective.Although construction cost is a dominating constraint in affordable shelters, their durability and strength are equally important. Project aims at evaluating various pr-fabrication technology on their role with perspective of strength-durability and cost. Optimization of the various parameters using Minitab software the optimal technology has been done. Although construction cost is a dominating constraint in affordable shelters , their durability and strength are equally important. Paper aims at presenting the evaluation of the design and optimization of the various parameters using structural analysis using Ansys workbench and minitab 18.0 software. Economic analysis is done and presented in paper.